Tuning of PID controller for air conditioning unit based on adaptive genetic algorithm - Zhou, Y.-T.; Nie, J.-B.; Han, N.; Li, D.; Chen, C. (Journal of Digital Information Management, 2013)
PID control is widely used in air conditioning system. The algorithm is simple but has a long response time, and the adjustment is not flexible. In this paper, we propose a method of optimizing PID controller parameters based on adaptive genetic algorithm. Specifically, the fitness function with penalty terms is added to the classical genetic algorithm and adaptive crossover and mutation factor genes to make the PID parameters converge to global optimum quickly. In addition, the method can prevent overshoot and improve stability effectively. Simulation results indicate that our method achieved a 83% reduction in regulation time of response of an airconditioning unit compared with the original PID system . The method can be used for online tuning of PID parameters as well.
Keywords: Adaptive genetic; Air-conditioning unit; Control system; Penalty factor; PID parameter optimizatio